2022
DOI: 10.1111/dme.15010
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, inactivity and sleep during the Diabetes Remission Clinical Trial (DiRECT)

Abstract: Aims:As sustained weight loss is vital for achieving remission of type 2 diabetes, we explored whether randomisation to weight loss plus maintenance in the DiRECT trial was associated with physical activity, inactivity or sleep.Methods: Participants were randomised to either a dietary weight management programme or best-practice care. The weight management group were encouraged to increase daily physical activity to their sustainable maximum. Objective measurement was achieved using a wrist-worn GENEActiv acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
7
1
1
Order By: Relevance
“…Both studies employed total diet replacement, with targets of approximately 800–850 kcal/day, and importantly, employed an active protocol-driven approach to medication removal. After 6 months, the DiRECT study re-introduced food [ 5 ] and provided advice to increase physical activity during the maintenance period [ 26 ]. Several other studies have observed similarly profound effects on HbA 1c with dietary replacement and intensive weight loss over a shorter time period than the DiRECT and Look AHEAD Studies [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both studies employed total diet replacement, with targets of approximately 800–850 kcal/day, and importantly, employed an active protocol-driven approach to medication removal. After 6 months, the DiRECT study re-introduced food [ 5 ] and provided advice to increase physical activity during the maintenance period [ 26 ]. Several other studies have observed similarly profound effects on HbA 1c with dietary replacement and intensive weight loss over a shorter time period than the DiRECT and Look AHEAD Studies [ 27 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predicted reduction in the resting energy rate in both trials is in accord with expectations and with other controlled weight loss studies that saw a 5.6–14.6% reduction in resting energy rate with similar weight loss ( 23 25 ). Lighter people must burn fewer calories unless more active and accelerometer data from DiRECT showed minimal change in activity ( 26 ). Notably, the improvement in cardiorespiratory fitness appeared to be rapid in DIADEM-I.…”
Section: Discussionmentioning
confidence: 99%
“…Weight reduction in overweight and obese people with type 2 diabetes results in the reduction of vascular risks, increases self-esteem, quality of life and can lead to remission in the early stages of type 2 diabetes 51 52 53 54 55 56 . In the current clinical practice guidelines in this supplement, there is an extensive section on obesity and diabetes 57 .…”
Section: Therapymentioning
confidence: 99%